The Experimental Analysis of Elastic Agitator Effects to Improve Turbulent Energy Transport - Yong, Tshun Howe (Curtin University, 2016)
This project explores the turbulence enhancement performance of a flexible agitator in replacing the conventional rigid agitator. Polymer EVA was chosen as the material for flexible while aluminium for the rigid agitator. A UVP was used to study the mean and fluctuating flow properties in the near wake of rigid and flexible agitators in the subcritical flow regime. Results show increased wake region, augmented turbulence production, turbulence intensity and Reynolds stresses by the flexible agitator.